Maternal Phthalate and Personal Care Products Exposure Alters Extracellular Placental miRNA Profile in Twin Pregnancies. (February 2019) - Zhong, Jia; Baccarelli, Andrea A.; Mansur, Abdallah; Adir, Michal; Nahum, Ravit; Hauser, Russ; Bollati, Valentina; Racowsky, Catherine; Machtinger, Ronit
Prenatal exposure to endocrine-disrupting chemicals (EDCs) exerts both short- and long-term adverse effects on the developing fetus. However, the mechanisms underlying these effects have yet to be uncovered. Maternal–fetal signaling is mediated in part by signaling molecules (eg, microRNAs [miRNAs]) contained in extracellular vesicles (EVs) that are released by the placenta into the maternal circulation. We investigated whether maternal exposure to the EDCs phthalates and personal care products alters the miRNA profile of placental-derived EVs circulating in maternal blood. Blood and urine samples from pregnant women with uncomplicated term dichorionic, diamniotic twin pregnancies were analyzed as part of a larger study investigating correlations between exposure of phthalate and personal care products and epigenetic alterations in twin pregnancies. We explored correlations between maternal urinary levels of 13 phthalate and 12 personal care products metabolites and the miRNA profile of placental EVs (EV-miRNAs) circulating in maternal blood. The expression of miR-518e was highest among women with high urinary levels of monobenzyl phthalate and methyl paraben. miR-373-3p was the least expressed in women exposed to high levels of methyl paraben, and miR-543 was significantly downregulated in women exposed to high levels of paraben metabolites, dichlorophenol metabolites, and triclosan. In conclusion, this pilot study reveals that prenatal exposure to EDCs is associated with altered profile of circulating placenta-derived EV-miRNAs. Further studies are needed to generalize these results to singleton pregnancies and to assess whether these alterations are associated with pregnancy complications.